Resilience of Parents of Young University Students with Disabilities - MacÃƒÂas, Eleticia Isabel Pinargote; Vaca, Francisco Ashley Gavilanes; GavilÃƒÂ¡nez, VÃƒÂctor Hugo CedeÃƒÂ±o (International Research Journal of Management, IT & Social Sciences, 2018)
The resilience of parents can play a decisive role as a resource that favors the inclusion and development of students with disabilities, representing a decisive contribution in school-family co-responsibility. This work showed a conceptual analysis related to resilience from a family dimension and especially the role played by parents. The research was carried out in the context of the Technical University of ManabÃ, a representative sample of students with disabilities and their families was selected, two instruments were applied to obtain the data: Family Functioning Scale [1] and the Mother Resilience Scale [2]. The attention to the young person with a disability was analyzed, and it is particularized in the related to the family of these. The results are shown in tables that allow the final results to be identified.